Application of Analytic Hierarchy Process in Determining Priorities to Reduce Food Loss and Food Waste in Indonesia - Elimawaty Rombe; Gatha Vesakha; Mustamin a; Suryadi Hadi (International Journal of Supply Chain Management, 2018)
This study aims to determine the extent of decision-making priorities by using green supply chain management model in overcoming the problem of food waste. This research focused on entities involved in supply chain management and identified their opinions in selecting the level of importance of green supply chain management model. This research applies AHP analysis and using Microsoft Excel which based on Windows 7 to analyse the priorities. Sub-criteria criteria are source, make, deliver, and return. While the sub-criteria are reliability, responsiveness, agility, cost and asset. After doing the research, sub criteria that dominates the formation of food waste is sub criteria deliver, then followed by sub criteria make, source and return. This research found that sub criteria deliver more dominant in donating food waste, followed by source, make and return. Then, in the criteria, the cost criteria are the dominating criteria, then followed by responsiveness, reliability, agility, and asset. This research is useful to acknowledge where the process on supply chain management that causes the occurrence of food waste, so that companies or other organizations can overcome the inefficiency of food in certain process.